2008
DOI: 10.1007/s11094-008-0159-x
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of ecdysteron-80 from Serratula coronata L. and assessment of its pharmacological action. Part I. Adaptogenic, gastroprotective, thermoprotective, and antihypoxic activity

Abstract: A method for extracting ecdysteroids from Serratula coronata L. for the new phytopreparation Edcysterone-80 is proposed. Experiments on white rats established that this preparation has pronounced adaptogenic, antihypoxic, gastroprotective, and thermoprotective properties. Results of this study can be applied both in basic research and in the development of production technology for the new pharmaceutical preparation based on ecdysteroids of Serratula coronata.Preparations of plant origin that have a broad spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…The results obtained before and after the application of the cream are presented in Figure 4. There are scientific reports which have suggested that phytoecdysteroids have antiinflammatory and antioxidant properties as well as a positive effect on metabolic diseases, infectious diseases and physical and mental weakness [3,8,11,12,[14][15][16][17][18]31]. Rosselli et al have shown that ecdysones have cytotoxicity potential against rat C6 glioma cells [32].…”
Section: Examination Of 2% Phytoecdysteroids Cream For Seborrheic Dermatitismentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained before and after the application of the cream are presented in Figure 4. There are scientific reports which have suggested that phytoecdysteroids have antiinflammatory and antioxidant properties as well as a positive effect on metabolic diseases, infectious diseases and physical and mental weakness [3,8,11,12,[14][15][16][17][18]31]. Rosselli et al have shown that ecdysones have cytotoxicity potential against rat C6 glioma cells [32].…”
Section: Examination Of 2% Phytoecdysteroids Cream For Seborrheic Dermatitismentioning
confidence: 99%
“…The compounds and materials in which they play a dominant role are very promising for phytotherapy [ 7 , 8 , 9 , 10 ]. Phytoecdysteroids have a positive effect on hypercholesterolemia, hyperglycemia, hypotension, infectious diseases and physical and mental weakness [ 8 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Puri et al have found that 20-beta-hydroxyecdysone is efficient in the prevention of hot flushes in ovariectomized rats [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1), found in plants such as Rhaponticum carthamoides, Serratula coronata, and Spinacia oleracea [6]. The prospect of studying the mechanism of action of 20 E is due to the lack of toxicity, and a manifestation of the tonic, anabolic, stress protective, gastroprotective, antihypoxic, and adaptogenic effects [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Besides these, increase in lactation, improvement of wound healing and epidermis regeneration was determined [10][11][12]37,38]. Various compositions of patented preparations have been designed for the prevention of rapid ageing, modulation of the course of diseases associated with old age, influence on obesity, atherosclerosis, hypertension (metabolic syndrome), complaints associated with menopause, andropause, and skin defects related to old age [39][40][41][42][43][44][45][46]. All these make ecdysterone seem like a universal medicinal substance, but this impression is not unique, as, for example flavonoids also interfere with the activity of a wide range of enzymatic systems.…”
mentioning
confidence: 99%